2018
DOI: 10.1002/cam4.1541
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analyses of a novel lncRNA‐associated signature as the prognostic biomarker for Hepatocellular Carcinoma

Abstract: Accumulating evidence implies that long noncoding RNAs (lncRNAs) play a crucial role in predicting survival for Hepatocellular carcinoma (HCC) patients. This study aims to capture the current research hotspots of HCC, based on the analysis of publications related to HCC research from 2013 to 2017, and to identify a novel lncRNA signature for HCC prognosis through the data mining in The Cancer Genome Atlas (TCGA). “Prognosis” and “biomarker” were located in the core of the HCC research hotspot. Moreover, long n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Several previous studies have also constructed risk scoring systems to predict the prognosis of patients with HCC (24)(25)(26)(27)(28)(29)(30)(31). However, those risk scoring systems were based on DElncRNAs between HCC and normal samples, while the risk scoring systems in the present study are based on the DElncRNAs between HCC Table IX.…”
Section: Discussionmentioning
confidence: 88%
“…Several previous studies have also constructed risk scoring systems to predict the prognosis of patients with HCC (24)(25)(26)(27)(28)(29)(30)(31). However, those risk scoring systems were based on DElncRNAs between HCC and normal samples, while the risk scoring systems in the present study are based on the DElncRNAs between HCC Table IX.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, it has been shown that most lncRNAs deregulated in cancer are tumor-specific, whereas only a handful behave as "onco-lncRNAs", deregulated across many cancer types [54,60,61]. This has encouraged the development of a whole new field for the exploration of lncRNAs in cancer as a source of novel molecular targets and as biomarkers for diagnosis [62], predictors of treatment response [63], disease-free and overall survival [64,65] and risk of metastasis [66]. Similarly, deregulation and functional implications of lncRNAs have been studied in many other diseases, including HCV infection.…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…In this study, several lncRNAs with the largest fold changes among DE lncRNAs were studied. For example, GBP1P1 is a lncRNA that acts as a prognostic biomarker for hepatocellular carcinoma [32]. MIR3142HG can regulate the in ammatory response following IL-1β-mediated activation of human lung broblasts, which is a positive regulator of IL-8 and CCL2 release [33].…”
Section: Mscs Are One Of the Most Important Immunoregulatory Cell Typmentioning
confidence: 99%